2021
DOI: 10.21203/rs.3.rs-998393/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Consumers' Awareness and Proposed Measures Against the Prevalence of Counterfeit Drugs in Developing Countries

Abstract: Background: Counterfeit drugs have been reported as the primary cause of increased morbidity and drug resistance in developing countries. However, consumers' awareness of the prevalence of fake drugs in developing countries remains unknown.Objectives: To assess consumers' awareness and the principal contributors of counterfeit drugs, propose measures to curb this menace in developing countries.Method: Data were collected using a questionnaire with 24 questions bordering on consumer awareness and measures taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This shows that most consumers and stakeholders in this study know about fake drugs. This was consistent with a study by Onuh et al (2022) [14] on assessing consumers' awareness and ability to identify counterfeit drugs in developing African countries, which found a high awareness of fake drugs in Nigeria. The same study found a low level of awareness among participants in Ghana and Pakistan.…”
Section: Consumers' and Stakeholders' Knowledge Of Substandard And Fa...supporting
confidence: 92%
“…This shows that most consumers and stakeholders in this study know about fake drugs. This was consistent with a study by Onuh et al (2022) [14] on assessing consumers' awareness and ability to identify counterfeit drugs in developing African countries, which found a high awareness of fake drugs in Nigeria. The same study found a low level of awareness among participants in Ghana and Pakistan.…”
Section: Consumers' and Stakeholders' Knowledge Of Substandard And Fa...supporting
confidence: 92%
“…A huge amount of medicines is sold via informal distribution methods in Africa and South America as well as in many parts of Asia; here, lacking education of the “health” personnel and little knowledge on the part of the patients regarding treatment errors, resistance, or falsified medicine merge into a very serious and complex problem. 92 Moreover, many countries do not have educational schemes for pharmacists and/or pharmaceutical scientists, as e.g. in Europe, Australia, Northern America, and some parts of Asia.…”
Section: Discussionmentioning
confidence: 99%